Implementation methodology of Activity-Based Costing for Micro, Small and Medium Enterprises in Paraguay, year 2020 (Journal on studies and research of academic knowledge, 2024)
In Paraguay, particularly, Micro, small and medium-sized enterprises (MSMEs) have difficulties in the preparation and design of their cost systems, in addition, Activity-Based Costing (ABC) is little known in our country, and mainly due to the type of mentioned companies. The general objective of this work was to design the Activity-Based Cost Implementation Methodology for Micro, Small and Medium Enterprises in Paraguay, year 2020. As a methodology, the mixed approach was applied with applicative and purposeful scope, a documentary analysis of the main cost exponents for the purposes of comparability and ABC cost proposal. The main results shows that a) The implementation of the CBA is complex in its beginnings, b) After its implementation, the CBA allows the correct identification of costs in detail for each type of unit or department of the MSME. It is concluded that the proposed methodology will benefit MSMEs for their correct restructuring and adaptation in terms of their cost systems.
Keywords: International Financial Reporting Standards; cost accounting; industrial companies; accounting experts; content analysis